Design and traction performance analysis of a mine deformable crawler pipeline robot - WANG Guorui; YAN Hongwei; KOU Ziming; WEI Hongmei; REN Haojie; MA Yaohui (Gong-kuang zidonghua)
The mine crawler pipeline robot, with its large contact area between the crawlers and the pipe wall, has strong obstacle-crossing ability and stability, making it suitable for complex and variable pipeline environments. Currently, mine crawler pipeline robots face issues such as complex structure, inability to actively control diameter variations, and poor traction and obstacle-crossing performance. A mine deformable crawler pipeline robot was proposed, which could adapt to pipeline environments with diameters ranging from DN180 to DN220. The robot included one central diameter-changing module and three crawler foot modules. Each crawler foot module was equipped with an independent drive motor, whose output shaft transmitted torque via bevel gears to drive the crawler foot synchronous wheels, thus providing forward propulsion for the robot body. The crawler foot modules were deformable and could be raised, allowing the robot to cross step-like obstacles. The central diameter-changing module could adjust the linkage extension and retraction through the motor and backpressure spring, ensuring the positive pressure between the crawler foot and the pipe wall, thus aligning the robot with the pipeline centerline and achieved flexible diameter variation. Traction dynamics models for the pipeline robot under horizontal, inclined, obstructed pipeline, and cable-dragging conditions was established. The analysis of the models revealed that the key to successful obstacle crossing was that the drive motors of the crawler foot modules must simultaneously meet three dynamic constraints: the lifting torque of the crawler foot, the rotational torque of the front wheel, and the forces required to overcome friction and cable-dragging resistance. Simulation results showed that: ① in an industrial pipeline environment simulation, the optimal spring coefficient for the robot body was found to be 4 N/mm. ② In an obstacle-crossing scenario simulation, the robot was able to cross an obstacle with a maximum step height of 15 mm, with the motor torque reaching its peak at approximately 340 N·mm. Experimental results showed that the robot's average traction force was 58 N, and it successfully crossed obstacles up to 15 mm high. During the obstacle-crossing process, the motor current remained stable, aligning with both the simulation results and the design requirements, thus verifying the rationality of the robot's structural design and confirming its excellent traction performance.